1989
DOI: 10.1111/j.1476-5381.1989.tb14608.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between structure and nicotine‐like activity: X‐ray crystal structure analysis of (−)−cytisine and (−)−lobeline hydrochloride and a comparison with (−)−nicotine and other nicotine‐like compounds

Abstract: 1 Although (-)-cytisine is a rigid structure, it occurs in the crystal in two distinct but very similar conformations in which the pyridone ring is tilted relative to the charged nitrogen atom at much the same angle as the pyridine ring is in (-)nicotine hydrogen iodide. The carbonyl group in the pyridone ring of (--cytisine, however, is on the side of the ring opposite to the pyridine nitrogen in (-)-nicotine. 2 The pKa of (-)-lobeline HCI at 250C is 8.6 (approx), indicating that (-)-lobeline is at least 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 39 publications
(48 reference statements)
4
57
0
Order By: Relevance
“…[100][101][102][103][104] Although lobeline has no structural resemblance to nicotine, and SARs do not suggest a common pharmacophore, 105 it has many nicotinelike effects, such as tachycardia and hypertension, 106 bradycardia and hypotension in anesthetized rats, 107 anxiolytic activity, 108 and improvement of learning and memory. 109 In contrast to nicotine, lobeline only marginally supports selfadministration in mice 110 and does not support self-administration in rats.…”
Section: Lobeline and Its Analogsmentioning
confidence: 99%
“…[100][101][102][103][104] Although lobeline has no structural resemblance to nicotine, and SARs do not suggest a common pharmacophore, 105 it has many nicotinelike effects, such as tachycardia and hypertension, 106 bradycardia and hypotension in anesthetized rats, 107 anxiolytic activity, 108 and improvement of learning and memory. 109 In contrast to nicotine, lobeline only marginally supports selfadministration in mice 110 and does not support self-administration in rats.…”
Section: Lobeline and Its Analogsmentioning
confidence: 99%
“…The nAChRs not readily available for cytisine binding could be the more membrane-immersed or aggregated receptors, accumulating in animals self-administering nicotine because of channel desensitization or other factors. The structure of cytisine is rigid and more conformationally restricted than that of epibatidine (Barlow and Johnson, 1989;Wei et al, 2003). Consequently, cytisine may not access the binding sites of closely grouped or partially compartmentalized nAChRs.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The standard resolution, room temperature crystal structures of cytisine (1) and N-methylcytisine (2) have been reported earlier [8,23,24]. Both alkaloids crystallize in noncentrosymmetric space group P 2 1 2 1 2 1.…”
Section: Resultsmentioning
confidence: 92%
“…It stimulates secretion of catecholamines, leading to increased blood pressure and sugar concentration, which alleviates nicotine withdrawal symptoms and stimulation of the respiratory system [2,7]. Comparison of the structures of nicotine and cytisine (Scheme 1) showed that the quasi-aromatic ring in cytisine and the pyridine ring in nicotine are associated in a similar way with respect to the nitrogen atom in the bispidine ring system (cytisine) and in the pyrrolidine ring (nicotine) [8]. Cytisine shows an affinity towards the specific subunits of nicotine acetylcholine receptors, nAChRs.…”
Section: Introductionmentioning
confidence: 99%